The Change of Identity of the Javanese Deli through a Marriage Ceremony - Leylia Khairani (Budapest International Research and Critics University, 2020)
The change in identity of the Javanese Deli was the result of a long historical journey consisting of several phases. The process of change was influenced by social interactions and processes that took place from the social conditions of the hometown, the migration to the plantations in Deli, to the outside of the plantation. The purpose of this research is how cultural identities are formed, constructed based on certain processes related to the history, context, and creativity of certain cultural actors to maintain their culture. The result of this research is that the culture of the Javanese Deli undergoes a process that is continuously being formed and changed. From this, it shows that the identity of the Deli Javanese is very much influenced by the changing situation and conditions compared to when they were in Java.